Decomposing Brazilian manufacturing industry dynamics in the mid-2000s: Macroeconomic factors and their sectoral impacts - Edson Paulo Domingues; Kênia Barreiro de Souza; Aline Souza Magalh\~aes (EconomiA, 2017)
The manufacturing industry's loss in participation, phenomena called “deindustrialization”, has been observed for the Brazilian economy for a while and seems to have intensified from mid-2000s. However, the literature has not developed a consistent or integrated analysis of this process. We have used a detailed simulation model to identify how macroeconomic factors (such as exchange rate, labor costs, and household consumption) have contributed to manufacturing dynamics. Our results indicate that the macroeconomic scenario explains a large portion of the manufacturing industry's participation loss. The rise in households consumption and investment, important factors in this period, were responsible for dampening of the pressures coming from the currency appreciation and the workforce costs, benefiting some industrial sectors, but not avoiding the manufacturings participation loss.
Keywords: O14; C68; D58; 330; Manufacturing; Growth; Development; Simulations